Conceptual design and performance evaluation of a hybrid concentrating photovoltaic system in preparation for energy. (15th March 2018) - Baig, Hasan; Siviter, J.; Li, W.; Paul, M.C.; Montecucco, A.; Rolley, M.H.; Sweet, T.K.N.; Gao, M.; Mullen, P.A.; Fernandez, E.F.; Han, G.; Gregory, D.H.; et al.
Abstract: Concentrating sunlight and focussing it on smaller sized solar cells increases the device's power output per unit active area. However, this process tends to increase the solar cell temperature considerably and has the potential to compromise system reliability. Adding a heat exchanger system to regulate this temperature rise, can improve the electrical performance whilst simultaneously providing an additional source of low temperature heat. In this study the performance of a low concentrator photovoltaic system with thermal (LCPV/T) extraction was conceptualised and evaluated in depth. An experimental analysis was performed using a first-generation prototype consisting of 5 units of Cross Compound Parabolic Concentrators (CCPC) connected to a heat extraction unit. A bespoke rotating table was used as experimental apparatus to effectively evaluate the optical performance of the system, as a function of its angular positions to replicate the motion of actual sun. Key design performance parameters for the LCPV/T collector are presented and discussed. This work also provides a useful technique to effectively calculate system performance, as a function of the orientation-dependant electrical characterisation parameters data. Finally, a Computational Fluid Dynamics (CFD) model was also applied to investigate the efficacy of the heat exchanger and hence estimate the overall co-generation benefit of using such optimisation techniques on realistic CPV systems. It was highlighted through these simulations that the water flow rate had the potential to be a critical power-generation optimisation criterion for LCPV-T systems. The maximum power output at normal incidence with concentrators and no water flow was found to be 78.4 mW. The system was found to perform with an average electrical efficiency ranging between 10 and 16% when evaluated at five different geographic locations. Experimental analysis of the data obtained showed an increase in power of 141% (power ratio 2.41) compared to the analogous non-concentrating counterpart. For example, in the case of London which receives an annual solar radiation of 1300 kWh/m 2 the system is expected to generate 210 kWh/m 2 . This may reduce further to include losses due to temperature, reflectance/glazing losses, and electrical losses in cabling and inverter by up to 36% leading to an annual power output of 134 kWh/m 2 of module. Highlights: Detailed proof of concept and manufacture of a CPV/T system. Coupled Optical and thermal analysis of the system. Impact of cooling on the performance of the CPV/T system. Experimental method to characterize the system as a function of azimuth and zenith angles.